Loss of intraepidermal nerve fiber density during SIV peripheral neuropathy is mediated by monocyte activation and elevated monocyte chemotactic proteins. Issue 1 (December 2015) - Lakritz, Jessica; Robinson, Jake; Polydefkis, Michael; Miller, Andrew; Burdo, Tricia
Abstract Background Peripheral neuropathy (PN) continues to be a major complication of human immunodeficiency virus (HIV) infection despite successful anti-retroviral therapy. Human HIV-PN can be recapitulated in a CD8-depleted, simian immunodeficiency virus (SIV)-infected rhesus macaque animal model, characterized by a loss of intraepidermal nerve fiber density (IENFD) and damage to the dorsal root ganglia (DRG). Increased monocyte traffic to the DRG has previously been associated with severe DRG pathology, as well as a loss in IENFD. Here, we sought to characterize the molecular signals associated with monocyte activation and trafficking to the DRGs. Methods Eleven SIV-infected CD8-depleted rhesus macaques were compared to four uninfected control animals. sCD14, sCD163, sCD137, regulated on activation normal T cell expressed and secreted (RANTES), and monocyte chemoattractant protein 1 (MCP-1) were measured in plasma and the latter three proteins were also quantified in DRG tissue lysates. All SIV-infected animals received serial skin biopsies to measure IENFD loss as well as BrdU inoculations to measure monocyte turnover during the course of infection. The number of BrdU+ and CD14+ CD16+ peripheral blood monocytes was determined by flow cytometry. The number of MAC387+, CCR2+, CCR5+, and CD137+ cells in DRG tissue was quantified by immunohistochemistry. Results sCD14, sCD163, MCP-1, and sCD137 increased significantly in plasma from pre-infection to necropsy. Plasma sCD163 and RANTES inversely correlated with IENFD. Additionally, sCD137 in DRG tissue lysate was elevated with severe DRG pathology and associated with the recruitment of MAC387+ cells to DRG. Elevated numbers of CCR5+ and CCR2+ satellite cells in the DRG were found, suggesting a chemotactic role of their ligands, RANTES, and MCP-1 in recruiting monocytes to the tissue. Conclusions We characterized the role of systemic (plasma) and tissue-specific (DRG) monocyte activation and associated cytokines in the pathogenesis of SIV-PN. We identified sCD163 and RANTES as potential biomarkers for HIV-PN, as these were associated with a loss of IENFD. Additionally, we identified CD137 signaling to play a role in MAC387+ cell traffic to DRG and possibly contribute to severe pathology. These studies highlight the role of monocyte activation and traffic in the pathogenesis of SIV-PN, while identifying specific signaling proteins for future pharmacological blockade.